Feasibility and acceptability of the smart pillbox and medication label with differentiated care to support person-centered tuberculosis care among ASCENT trial participants – A multicountry study - Tadesse, Amare W.; Mganga, Andrew; Dube, Tanyaradzwa N.; Alacapa, Jason; van Kalmthout, Kristian; Letta, Taye; Mleoh, Liberate; Garfin, Anna M. C.; Maraba, Noriah; Charalambous, Salome; Foster, Nicola; Jerene, Degu; et al. (Frontiers in Public Health, 2024)
Introduction: Digital adherence technologies (DATs) can offer alternative approaches to support tuberculosis treatment medication adherence. Evidence on their feasibility and acceptability in high TB burden settings is limited. We conducted a cross-sectional survey among adults with drug-sensitive tuberculosis (DS-TB), participating in pragmatic cluster-randomized trials for the Adherence Support Coalition to End TB project in Ethiopia (PACTR202008776694999), the Philippines, South Africa and Tanzania (ISRCTN 17706019). Methods: From each country we selected 10 health facilities implementing the DAT intervention (smart pillbox or medication labels, with differentiated care support), ensuring inclusion of urban/rural and public/private facilities. Adults on DS-TB regimen using a DAT were randomly selected from each facility. Feasibility of the DATs was assessed using a standardised tool. Acceptability was measured using a 5-point Likert-scale, using the Capability, Opportunity, Motivation, Behaviour (COM-B) model. Mean scores of Likert-scale responses within each COM-B category were estimated, adjusted for facility-level clustering. Data were summarised by country and DAT type. Results: Participants using either the pillbox (n=210) or labels (n=169) were surveyed. Among pillbox users, phone ownership (79%), use of pillbox reminders (87%) and taking treatment without the pillbox (22%) varied by country. Among label users, phone ownership (81%), paying extra to use the labels (8%) and taking treatment without using labels (41%) varied by country. Poor network, problems with phone charging and access, not having the pillbox and forgetting to send text were reasons for not using DATs. Overall, people with TB had a favourable impression of both DATs, with mean composite scores between 4·21 to 4·42 across COM-B categories. Some disclosure concerns were reported. Conclusion: From client-perspective, pillboxes and medication labels with differentiated care support were feasible to implement and acceptable in variety of settings. However, implementation challenges related to network, phone access, stigma, additional costs to people with TB to use DATs need to be addressed.